2012
DOI: 10.1371/journal.pcbi.1002687
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Correlation Networks from Genomic Survey Data

Abstract: High-throughput sequencing based techniques, such as 16S rRNA gene profiling, have the potential to elucidate the complex inner workings of natural microbial communities - be they from the world's oceans or the human gut. A key step in exploring such data is the identification of dependencies between members of these communities, which is commonly achieved by correlation analysis. However, it has been known since the days of Karl Pearson that the analysis of the type of data generated by such techniques (refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
1,968
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 2,058 publications
(1,996 citation statements)
references
References 28 publications
28
1,968
0
Order By: Relevance
“…In contrast with other studies, examining soil and sediment-bound microbial communities (Bissett et al, 2013;Sun et al, 2013), which have observed a lack of correlations between absolute abiotic measurements and 16S rRNA OTU relative abundances, numerous correlations were observed between biotic and abiotic factors. Although consideration should be made that such approaches, wherein relative abundances are used to derive correlations between species, may overestimate the numbers of true correlations (Friedman, 2012;r14933), this analysis was effective at classifying factors characteristic of the three observed periods, namely summer, autumn and winter periods, also observed in the dbRDA analysis (Figure 2). In this context, with cyanobacterial cell counts as the driver, 16S rRNA gene OTUs, cell counts and abiotic data were considered to be associated with each of the distinct periods when the observed variables exhibited strong positive correlations to either the cell counts or to one another ( Figure 5).…”
Section: Eubacterial Diversity and Compositionmentioning
confidence: 99%
“…In contrast with other studies, examining soil and sediment-bound microbial communities (Bissett et al, 2013;Sun et al, 2013), which have observed a lack of correlations between absolute abiotic measurements and 16S rRNA OTU relative abundances, numerous correlations were observed between biotic and abiotic factors. Although consideration should be made that such approaches, wherein relative abundances are used to derive correlations between species, may overestimate the numbers of true correlations (Friedman, 2012;r14933), this analysis was effective at classifying factors characteristic of the three observed periods, namely summer, autumn and winter periods, also observed in the dbRDA analysis (Figure 2). In this context, with cyanobacterial cell counts as the driver, 16S rRNA gene OTUs, cell counts and abiotic data were considered to be associated with each of the distinct periods when the observed variables exhibited strong positive correlations to either the cell counts or to one another ( Figure 5).…”
Section: Eubacterial Diversity and Compositionmentioning
confidence: 99%
“…Also, as microbes live in communities, there are likely three-feature interactions, four-feature interactions and more. An additional challenge is that microbial sequence data provide relative abundances based on a fixed total number of sequences rather than absolute abundances, which introduces the problem of compositions (Lovell et al, 2010;Friedman and Alm, 2012). Sparsity of the features and missing data owing to incomplete sampling further complicates statistical analysis (Reshef et al, 2011;Friedman and Alm, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An additional challenge is that microbial sequence data provide relative abundances based on a fixed total number of sequences rather than absolute abundances, which introduces the problem of compositions (Lovell et al, 2010;Friedman and Alm, 2012). Sparsity of the features and missing data owing to incomplete sampling further complicates statistical analysis (Reshef et al, 2011;Friedman and Alm, 2012). Finally, microbes may display diverse types of relationships, such as linear, exponential or periodic, and most tests are not general enough to detect them all; even those that do are unlikely to detect different functions with the same efficiency (Reshef et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Effect of hamster microbiota on C. difficile M Miezeiewski et al (Friedman and Alm, 2012). Interesting phyla generally considered as environmental, such as the recently described Armatimonadetes (Tamaki et al, 2011) were not only encountered in the fecal samples but demonstrated significant increase in relative abundance after antibiotic application.…”
Section: Effect Of Clindamycin Treatment On Fecal Extracts In In Vitrmentioning
confidence: 99%